Possibilities of Using the Internet of Things to Improve Communication between Users and Manufacturers - Michal TECZKE (Communications of International Proceedings, 2021)
In the study, the author focuses on two main aspects. In the theoretical part, he presents a definition of the Internet of Things based on a selection of the most cited sources. To then move on to bibliometric analysis. This analysis aims at indicating the development of the concept of the Internet of Things in contemporary literature and determining to what extent this concept is used in business, economics and management. The conducted research is to indicate the research gap that the author tries to fill in the second part of the article with conclusions from the empirical research. The primary study was conducted on a group of 701 adult Poles, and additionally on a group of 262 residents of countries other than Poland. It aimed at verifying whether there is a potential to use smart devices to share opinions with manufacturers on the perceived satisfaction with the use of products, and whether it is possible to identify the largest barriers limiting this type of contact.
Keywords: Internet of Things; Consumer-Producer (C2P) Relations; Communication